Sintomas urinários e sexuais em mulheres submetidas à histerectomia por câncer de colo uterino: prevalência e impacto na qualidade de vida - Firmeza, Mariana Alves (2021)
Cervical cancer is one of the most important types of cancer in women. Although the survival outcome for cervical cancer treated with early-stage negative lymph nodes is excellent, hysterectomy carries important morbidity, particularly with regard to urinary and sexual functions. This study aimed to evaluate the effects of hysterectomy for cervical cancer on urinary and sexual functions, as well as the impacts of these dysfunctions on the patients' quality of life. A cohort study was carried out in a reference hospital located in the city of Fortaleza/CE. Data collection took place from July 2020 to February 2021 and the sample consisted of women who met the following inclusion criteria: age between 18 and 64 years and indication for hysterectomy. The following were excluded from the sample: women with neurological disorders, history of previous pelvic surgeries (urological, gynecological or proctological) and with an indication for hysterectomy due to cancer other than that of the uterine cervix. Thus, a total sample of 71 patients was obtained, 31 oncologic (G-CCU) and 40 with benign diseases (G-PB). Six instruments were used for data collection: an instrument developed by the author for the collection of sociodemographic, clinical and gynecological-obstetrical data, an instrument structured according to the ICS/IUGA recommendations for investigating voiding complaints and another for investigating complaints sexual; the Female Sexual Function Index (FSFI); the King's Health Questionnaire (KHQ) and the 36-Item Short Form Health Survey (SF-36) to assess quality of life. This study was organized in 3 stages: 1) Preoperative: assessment of urinary and sexual complaints and quality of life; 2) 1st postoperative month: assessment of urinary complaints and quality of life by telephone; 3) 4th month after surgery: evaluation of urinary and sexual complaints. Women in both groups started with similar percentages of urinary complaints (G-CCU:32.5%; G-PB:32.3%; p>0.05), however the percentage of these dysfunctions practically doubles during the first month in the G-CCU and this increase is maintained in the fourth month in relation to the baseline for women in this group (61.3%; p=0.012). Regarding sexual dysfunctions, a higher percentage of women in the G-PB declared to have an active sexual life at the time of data collection, which had higher rates of sexual complaints (G-PB: 82.5%; G-CCU: 54 .8%; p=0.011). However, four months after performing the hysterectomy, the percentages of these complaints are similar between the groups. The participants in this research already had some urinary and sexual symptoms before the surgical approach, however, even in the presence of confounding factors (parity, for example), in the postoperative period of hysterectomy, these rates were higher. In addition, when comparing the G-CCU and G-PB, the prevalence of voiding and sexual dysfunctions was more prevalent in the former. With regard to quality of life, both general and specific, patients diagnosed with CCU had their quality of life lower postoperatively, compared to baseline and G-BP.